Early Warning System Technology Innovation Study in Flood Disaster Mitigation in Aren Village Area Bontang Disability - Nikita Adriyani; Rio Jumardi; Al Rosyid Anggi Satrya; Zaini Zaini (STKIP Singkawang, 2019)
AWLR with the application of I Am Aren is been CSR program of PT Pupuk Kaltim that was developed as a flood disaster mitigation in order to be able to minimize the loss of society cause of flooding. Obtaining data used black-box testing techniques, surveys, and interviews which are then analyzed inductively. Respondents involved as many as 40 people for the survey and 20 people for the interview. The research approach used qualitative research. The results showed that the black-box testing for the recording feature was following the procedure and could provide accurate information. Respondents did not undergo problems in the using and the results of the implementation of the tool were able to reduce losses to 74.4% from the previous loss.